Francis Winslow papers - Winslow, Francis, 1818-1862.
Correspondence, journals, logs, and other papers documenting Winslow's naval career. Includes journal (1834-1837) kept during his first cruise aboard the USS Brandywine (Frigate) to South America, subsequent shore duty in Rio de Janeiro, Brazil, Montevideo, Uruguay, Buenos Aires, Argentina, and aboard the USS Erie (Sloop of war); journals and logs recording his experiences aboard the USS Marion (Sloop of war) and USS Dale (Sloop of war) in South American waters (1839-1842) and cruises (1854-1859) on the USS Falmouth (Sloop of war) and USS Saratoga (Sloop of war) and the USS Merrimack (Frigate); and letterbook (1861-1862) from his commands of the USS Water Witch (Steamer) and USS R. R. Cuyler (Steamer) during the Civil War blockades of Alabama, Florida, and Louisiana ports. Correspondents include his wife, Mary Sophia Nelson Winslow, and other family members.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Winslow, Mary Sophia Nelson, -- 1827- -- Correspondence; Winslow family -- Correspondence; Brandywine (Frigate); Dale (Ship); Erie (Sloop of war); Falmouth (Ship); Marion (Ship); Merrimack (Frigate); R.R. Cuyler (Ship); Saratoga (Sloop of war); Water Witch (Steamer); United States. -- Navy -- Cruise, 1834-1837.; United States. -- Navy -- Cruise, 1854-1859.; United States. -- Navy -- Foreign service -- South America; United States. -- Navy -- History; United States. -- Navy -- Officers; Harbors -- Alabama; Harbors -- Florida; Harbors -- Louisiana; Logbooks -- United States -- 19th century; Alabama -- History -- Civil War, 1861-1865 -- Blockades; Argentina -- Description and travel; Brazil -- Description and travel; Buenos Aires (Argentina) -- Description and travel; Florida -- History -- Civil War, 1861-1865 -- Blockades; Louisiana -- History -- Civil War, 1861-1865 -- Blockades; Montevideo (Uruguay) -- Description and travel; Rio de Janeiro (Brazil) -- Description and travel; South America -- Description and travel; United States -- History -- Civil War, 1861-1865 -- Blockades; United States -- History -- Civil War, 1861-1865 -- Naval operations; United States -- History, Naval; Uruguay -- Description and travel; Naval officers